Perempuan dalam Gereja Pentakosta Tabernakel dan Gereja Katolik: Boleh Kah Ditahbiskan Menjadi Pendeta atau Pastor ? - Sanga, Laurensius Dihe -; Tafonao, Talizaro -; Waruwu, Septerianus - (Sekolah Tinggi Teologi Berea, Salatiga, 2022)
Every Christian Church has various reasons why women are not ordained as priests or pastors. Of the many churches, the author focuses attention on the Tabernacle Pentecostal church and the Catholic Church. The purpose of writing this article is to offer a new perspective to the Church that does not ordain women to become pastors or become priests. The author would like to invite to reflect that by not ordaining women to become priests or priests, will there not be a stunting of women's roles? The method used in this writing is literary narrative. The author tries to dig from the literature of books, journals and theses as well as interviewing several religious leaders about why women should not be ordained as priests or priests. However, the author wants to highlight aspects of Feminism Theology and the biblical basis as a frame of reference to convince readers that women are also the image of God. Thus, in essence, women have the same dignity in the eyes of God as people who have gifts.